Verrucous carcinoma arising from a previous cystic lesion: a case report - Sunghyun Kang; Dae Ho Leem (SpringerOpen, 2018)
Abstract Background Verrucous carcinoma (VC) accounts for 1-10% of cases of squamous cell carcinoma (SCC) in the oral cavity, and 75% of VC occur in the oral cavity. Only 3% of primary intraosseous squamous cell carcinomas (PIOSCC), which means SCC occurring primarily in the bone, are VC. Verrucous carcinoma arising from odontogenic cysts (OC) is very rare, with only seven cases reported to date. Case presentation This study reported a case of a patient who underwent partial maxillectomy and neck dissection for VC that occurred in the right anterior maxilla. The patient was admitted to the emergency department at our institution 8 years ago and showed cystic lesions in the anterior maxilla on facial computed tomography (CT) images. Treatment through other departments including assessment of laceration in the mental region and only suture was performed. This report highlights a very rare case of VC in the right anterior maxilla arising from a previous cystic lesion. Conclusions Since PIOSCC can arise from OC, appropriate treatment of intraosseous cysts and regular radiologic evaluation are necesssary. Surgical exicision of the primary lesion without neck dissection can lead to good prognosis for patients with primary intraosseous verrucous carcinoma.